2022
DOI: 10.1016/j.diabres.2022.109232
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the impact of glycaemic status on clinical outcomes and anti-SARS-CoV-2 antibody responses among patients with predominantly non-severe COVID-19

Abstract: Aims We carried out this prospective study of predominantly non-severe COVID-19 patients, to evaluate the influence of glycaemic status on clinical outcomes and neutralising antibody (Nab) responses, potentially relevant to the COVID-19 vaccination programme. Methods We included consecutive adults admitted to Queen Mary Hospital for COVID-19 from July 2020–May 2021. Glycaemic status was defined by admission HbA1c. Clinical deterioration was defined by radiological progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Patients with COVID‐19, who survive until discharge from the hospital, may still be at increased risk of adverse outcomes. Some patients demonstrate biomarkers for residual hypercoagulability (high D‐dimer), 55 and elevated inflammatory response (high C‐reactive protein), 57 which might increase post‐discharge risk of thromboembolic events and death in the convalescence. One RCT showed that prophylactic dose of a DOAC (rivaroxaban) compared to no anticoagulation reduced risk of non‐fatal or fatal VTE without a significant increase in bleeding risk 56 .…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Patients with COVID‐19, who survive until discharge from the hospital, may still be at increased risk of adverse outcomes. Some patients demonstrate biomarkers for residual hypercoagulability (high D‐dimer), 55 and elevated inflammatory response (high C‐reactive protein), 57 which might increase post‐discharge risk of thromboembolic events and death in the convalescence. One RCT showed that prophylactic dose of a DOAC (rivaroxaban) compared to no anticoagulation reduced risk of non‐fatal or fatal VTE without a significant increase in bleeding risk 56 .…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…First, some COVID-19 patients or vaccine recipients do not develop su cient protective antibody responses. Lower neutralizing antibody (NAb) titers are found in patients with asymptomatic or mild COVID-19, immunocompromised patients and older adults 10,11,12,13,14,15,16 . Second, the NAb titers elicited by inactivated whole virion or adenovirus-vectored vaccines are lower than those elicited by mRNA vaccines 17,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Critical disease was defined by respiratory failure requiring mechanical ventilation, shock, and intensive care unit admission. C-reactive protein (CRP) levels during hospitalization for COVID-19 were retrieved with CRP >0.76 mg/dL considered elevated [15].…”
Section: Participantsmentioning
confidence: 99%
“…HbA1c was measured in whole blood using cation-exchange high-performance liquid chromatography. The assay was certified by National Glycohemoglobin Standardization Programme and standardized to Diabetes Control and Complications Trial reference assay [15]. Insulin levels were measured using Human Insulin Quantikine enzyme-linked immunosorbent assay (ELI-SA) kit (R&D Systems Inc., Minneapolis, MN, USA) with intraassay coefficient of variability (CV) of 3.7%-4.0% and inter-assay CV of 6.9%-7.5%.…”
Section: Biochemical Assessmentsmentioning
confidence: 99%